Comparison of Telomere Length in Age-Matched Primiparous and Multiparous Brahman Cows - Sydney E. O’Daniel; Kelli J. Kochan; Charles R. Long; David G. Riley; Ronald D. Randel; Thomas H. Welsh (Animals, 2023)
Physiological and psychological stressors have been associated with the attrition of telomeres, which are the protective caps of chromosomes. This study compares the telomere length (TL) in 4-year-old Brahman cows grouped by the first parity (n = 8) and the second parity (n = 11). The cows were bled via jugular venipuncture, weighed, and had their body condition scores recorded at Day −28 prior to calving and at Day + 7 and Day + 28 post-calving. The duration of labor (Dlabor) and parturition ease were recorded. The peripheral leukocytes were isolated, the leukocyte blood count with differential was recorded, and the genomic DNA was extracted. The relative quantity of telomere products, which is proportional to the average TL, was determined via multiplex quantitative PCR using the ratio (T/S ratio) of bovine telomere and β-globulin DNA. Standards of the bovine telomere (1012–107 dilution series) and β-globulin (109–104 dilution series) genes were utilized to produce relative copy numbers. The samples were assayed in triplicate and were included if the triplicate Cq difference was less than 0.25 cycles. The parity was the fixed effect, and the random effects included the sire and day repeated with the cow as the subject. Statistical significance was not observed in the leukocyte number or type (p > 0.1). A reduction in the TL of approximately 9225 telomeric copies was found between Parity 1 and Parity 2 (p = 0.02). A trend was found between the TL and Dlabor (p = 0.06). The stress of parturition and raising the first calf of a cow’s life may be responsible for TL attenuation. Parity may be considered a stressor of cow longevity.